Phase-imaging ion-cyclotron-resonance measurements for short-lived nuclides - Eliseev, Sergey; Blaum, K.; Block, M.; Droese, C.; Goncharov, Mikhail Leonidovich; Minaya Ramirez, E.; Nesterenko, D. A.; Novikov, Yu. N.; Schweikhard, L. (Physical review letters, 2013)
A novel approach based on the projection of the Penning-trap ion motion onto a position-sensitive detector opens the door to very accurate mass measurements on the ppb level even for short-lived nuclides with half-lives well below a second. In addition to the accuracy boost, the new method provides a superior resolving power by which low-lying isomeric states with excitation energy on the 10-keV level can be easily separated from the ground state. A measurement of the mass difference of 130Xe and 129Xe has demonstrated the great potential of the new approach.
Gesehen am 01.02.2021